Smaller kidney size at birth in South Asians: findings from the Born in Bradford birth cohort study - Roderick, Paul J. (Nephrol Dial Transplant, 2016)
BACKGROUND: Rates of advanced chronic kidney disease and renal replacement therapy are higher in South Asian than in white British populations. Low birth weight is also more frequent in South Asian populations and has been associated with increased risks of kidney disease, perhaps due to a reduced nephron endowment. METHODS: Using ultrasound scans at 34 weeks of gestation, we measured fetal kidney dimensions (transverse and anteroposterior diameters, length and circumference) and derived volume in a random sample of 872 white British and 715 South Asian participants in the Born in Bradford cohort study. Kidney measurements were compared between ethnic groups. RESULTS: Birth weight for gestational age at 40 weeks was 200 g less in South Asian babies compared with white British babies. The mean kidney volume for gestational age was 16% lower in South Asian than in white British babies [8.79 versus 10.45 cm(3), difference 1.66 cm(3) (95% confidence interval 1.40–1.93, P < 0.001)]. The difference was robust after adjustment for maternal age, socio-economic factors, marital status, body mass index, smoking and alcohol use in pregnancy, parity, baby's gender and birth weight for gestational age [adjusted difference 1.38 cm(3) (0.97–1.84), P < 0.001]. There were smaller reductions in other fetal measures. CONCLUSION: South Asian babies have smaller kidneys compared with white British babies, even after adjusting for potential confounders including birth weight. This finding may contribute to increased risks of adult kidney disease in South Asian populations.